Parkinson's disease-associated DJ-1 mutations impair mitochondrial dynamics and cause mitochondrial dysfunction - Wang, Xinglong; Petrie, Timothy G.; Liu, Yingchao; Liu, Jun; Fujioka, Hisashi; Zhu, Xiongwei (Journal of neurochemistry, 2012)
J. Neurochem. (2012) 121, 830–839. Mitochondrial dysfunction represents a critical event during the pathogenesis of Parkinson’s disease (PD) and expanding evidences demonstrate that an altered balance in mitochondrial fission/fusion is likely an important mechanism leading to mitochondrial and neuronal dysfunction/degeneration. In this study, we investigated whether DJ‐1 is involved in the regulation of mitochondrial dynamics and function in neuronal cells. Confocal and electron microscopic analysis demonstrated that M17 human neuroblastoma cells over‐expressing wild‐type DJ‐1 (WT DJ‐1 cells) displayed elongated mitochondria while M17 cells over‐expressing PD‐associated DJ‐1 mutants (R98Q, D149A and L166P) (mutant DJ‐1 cells) showed significant increase of fragmented mitochondria. Similar mitochondrial fragmentation was also noted in primary hippocampal neurons over‐expressing PD‐associated mutant forms of DJ‐1. Functional analysis revealed that over‐expression of PD‐associated DJ‐1 mutants resulted in mitochondria dysfunction and increased neuronal vulnerability to oxidative stress (H2O2) or neurotoxin. Further immunoblot studies demonstrated that levels of dynamin‐like protein (DLP1), also known as Drp1, a regulator of mitochondrial fission, was significantly decreased in WT DJ‐1 cells but increased in mutant DJ‐1 cells. Importantly, DLP1 knockdown in these mutant DJ‐1 cells rescued the abnormal mitochondria morphology and all associated mitochondria/neuronal dysfunction. Taken together, these studies suggest that DJ‐1 is involved in the regulation of mitochondrial dynamics through modulation of DLP1 expression and PD‐associated DJ‐1 mutations may cause PD by impairing mitochondrial dynamics and function. Abnormal mitochondrial dynamics is implicated in neurodegenerative diseases. We found that expression of PD‐associated DJ‐1 mutants resulted in excessive mitochondrial fragmentation via increased DLP1 expression, which in turn leads to mitochondrial dysfunction and increased neuronal susceptibility to H2O2 or MPP+. Expression of WT DJ‐1 caused mitochondrial elongation and protection. These studies suggest that impaired mitochondrial dynamics underlies neuronal dysfunction/degeneration caused by DJ‐1 mutations.